Partial replacement of fish meal by soybean meal supplemented with inulin and oligofructose in the diet of pikeperch (Sander lucioperca): Effect on growth and health status - Dadras, Hadiseh; Chupani, Latifeh; Imentai, Aiman; Malinovskyi, Oleksandr; Esteban, Maria Angeles; Penka, Tomas; Kolářová, Jitka; Rahimnejad, Samad; Policar, Tomáš (Frontiers in Marine Science, 2022)
The present study investigated the effect of partial substitution of soybean meal (SM) for fish meal (FM) with or without addition of inulin and oligofructose in pikeperch feed. A diet containing FM was considered as the basal diet, and then three other diets were prepared by: 1) replacing 50% of FM with SM (SM50), 2) replacing 50% of FM with SM and supplementation of 2% inulin (SMI50), and 3) replacing 50% of FM with SM and supplementation of 2% oligofructose (SMO50). Each diet was fed twice daily to triplicate groups of fish (36.68 ± 0.36 g) for eight weeks. The group fed SMO50 showed the highest weight gain (WG; 85.85 ± 4.46%) among the groups fed SM, with no significant difference from the FM group (79.74 ± 2.04%; p > 0.05). Specific growth rate (SGR) showed no significant differences among fish fed SMI50 (0.81 ± 0.07%), SMO50 (1.01 ± 0.09%) and FM (1.05 ± 0.02%). However, a lower SGR (0.69 ± 0.09%) was observed in the SM50 group without the supplementation of 2% inulin or oligofructose compared to the group fed FM (p < 0.05). The groups fed SMI50 and SMO50 showed no significant difference in FCR (1.23 ± 0.10; 0.91 ± 0.05, respectively) compared to the group fed FM (0.97 ± 0.04). While, a significant difference in FCR was found between the SM50-fed group without supplementation of inulin or oligofructose (1.50 ± 0.13) and the group fed FM (0.97 ± 0.04). Survival rate and whole-body composition showed no significant difference among all groups (p > 0.05). A significant decrease in serum total cholesterol concentration was observed in the SMO50 group (2.10 ± 0.29 mmole L-1) compared to the FM-fed group (3.33 ± 0.33 mmole L-1). Serum triglyceride showed a significant decrease in the groups fed SMI50 (0.98 ± 0.17 mmole L-1) compared to the group fed SMO50 (1.93 ± 0.24 mmole L-1). The concentrations of other serum biochemical parameters (total protein, glucose, lactate dehydrogenase, alanine aminotransferase, aspartate aminotransferase, and alkaline phosphatase) were not significantly affected by the dietary treatments (p > 0.05). Among all innate immunity and antioxidant parameters, only the serum malondialdehyde (MDA) concentration of SM50-fed fish (4.25 ± 0.7 nmole mL−1) was significantly lower than in the FM-fed group (with the highest MDA concentration; 25.17 ± 3.13 nmole mL−1). Serum total antioxidant capacity (T-AOC), superoxide dismutase (SOD), and catalase (CAT) were not significantly affected by the feeding (p > 0.05). Serum D-lactate concentration was not significantly affected by the dietary treatments (p > 0.05). No significant differences were found in the relative expression of IGF-I, IGF-II, GHR genes among the studied groups (p> 0.05). The results of the present study show that 50% replacement of FM with SM supplemented with a small amount of oligofructose (2% of dry matter) does not compromise the growth performance or the immune system of pikeperch. This substitution is feasible and provides a reference for cost-optimized design of feed formulation for pikeperch.